صورة الأجنبي في رحلة محمد أسد الطريق إلى مكة - قراش, العالية (كلية الأدب العربي والفنون, 2024)
الرواية تدخل في أدب الرحلات وكتب السيرة الذاتية، فهي مذكرات حية بكل ما تحمله الكلمة من معنى فالرجل يروي ما مر به من أحداث ترحاله المتواصل، حيث انتقل من عالم إلى عالم آخر ليس من خلال تغيير القناعات والانتماء فحسب، وإنما أيضا الانتقال الجسدي والبيئي والاجتماعي ليعيش بعقله وروحه وسلوكه وعواطفه وحياته اليومية في عالمه الجديد ، عالم الإسلام والعرب والجزيرة العربية، فقد جاء كتابا إسلاميا يساعد الغربي الذي يبحث عن الحقيقة ويريد أن يعرف الإسلام والمسلمين على حقيقته . تناولت هذه الدراسة "صورة الأجنبي في رحلة محمد أسد الطريق الى مكة" التي جزأناها إلى مدخل وفصليين تطبيقيين حيث تطرقنا في المدخل إلى مفهوم أدب الرحلة والصورة وارتأينا في الفصل الأول إلى إظهار صورة العرب والمسلمين أما الفصل الثاني فتناولنا فيه صورة الغرب ونظرته العدائية إلى الإسلام والمسلمين، وقد ثم تتويج البحث في الأخير بخاتمة احتوت أهم النتائج المتوصل إليها The novelfallsinto the genre of travelliterature and autobiographies, itis a living memoir in everysense of the word, the man recounts the events of his continuous displacement, as he moved from one world to another, not only through changes in beliefs and affiliations but also through physical, environmental, and social transitions, living with his mind, spirit, behavior, emotions, and daily life in his new world - the world of islam, Arabs, and the Arabian peninsula. This book serves as an Islamic guide for westerners seeking the truth and wanting to understand islam as it is. This study addresses "The image of the Foreigner in Muhammad Asad's journey to Mecca, which we divided into an introduction and two applications, in the introduction, we discussed the concept of travel literature and imagery, while in the first chapter, we aimed to portray of Arabs and Muslims. The second chapter dealt with the image of the west and its propagandistic view of islam and Muslims. Finally, the research culminated in a conclusion that highlighted the most significant findings.
Keywords: أدب الرحلة - الصورائية - محمد أسد - الإسلام-الغرب; travel literature – imagery – Mohammad Asad Islam – fanaticism.